BODY OF DEMOCRATIC CIVILIAN CONTROL OVER THE DEFENSE FORCES - Degtyarov, D. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2021)
The purpose of writing this article is to define the concept and features of democratic civilian control over the defense forces. It was found that the legal relations that arise during the consolidation and definition of the subject of democratic civil control are complex and governed by the rules of various branches of law. To correctly determine the subject of the studied type of control, it is necessary to distinguish the external manifestations of activity of these officials, which are subject to measurement, generalization and analysis. One such manifestation is the behavior of persons subject to legislative provisions on the exercise of democratic civilian control over the defense forces. The subject of democratic civilian control over the defense forces is an element of the objects of control, which is directly covered by the organizational behavior of both military officials and other categories of servicemen and employees of military formations, as well as civilians empowered by Ukrainian law to make decisions. relating to the defense forces. The subject of democratic civilian control over the defense forces must meet the following requirements: objectivity, measurability, specificity, repeatability of results in the case of application by other subjects of control of the same control methodology. The subject of democratic civilian control over the defense forces has its source in the social relations that arise in the security and defense sector. The relationship between the object and the subject of the specified control is determined by the scale of activities carried out to achieve the objectives of control. At the same time, the subject of democratic civilian control over the defense forces is always smaller in scale than its object. An analysis of the current legislation governing the control of the defense forces shows that a sufficient legal basis for the implementation of the above requirements has not yet been created. Gaps in the legal regulation of security and defense control activities need to be filled. This requires amendments to the Law of Ukraine "On National Security", aimed at specifying the system of evaluation of the results of control over the activities of the defense forces.